Sprinkler irrigation system for tea frost protection and the application effect - Yongguang, Hu; Chen, Zhao; Pengfei, Liu; Amoah, Asante Eric; Pingping, Li (International Journal of Agricultural and Biological Engineering, 2016)
Abstract: A sprinkler irrigation system was designed and applied for a tea field to achieve frost protection through latent heat released when water turning into ice. Frost protection effects during night were tested at different irrigation application rates by monitoring air temperature around tea canopy (Tc). Temperature sensors were arranged at different distances from the sprinkler. The preliminary results showed that, when the sprinkler system worked continuously at the application rate of 2-4 mm/h before sunrise, tea canopy was covered with ice and Tc remained around 0°C, preventing tea plants from frost damage. But no more temperature rise was obviously observed at the application rates above 4 mm/h, which means less cost effectiveness. The system was stopped after sunrise when background air temperature rose back to 0°C and Tc increased by 2.2°C in one hour, while Tc of non-irrigated area increased by 4.8°C, which might cause thawing injuries to tea plants. The leaf surface temperature was lower than Tc, and the difference between the leaf surface temperature and Tc decreased with the increase of application rate. Therefore, the sprinkler irrigation system could achieve tea frost protection, and the recommended application rate was 2-4 mm/h for better protection effect. The system should keep running throughout frost night till half an hour after sunrise. The start and stop of the sprinkler irrigation system should be controlled based on Tc. Keywords: sprinkler irrigation, frost protection, Camellia Sinensis L, application rate, temperature rise, frost damageDOI: 10.3965/j.ijabe.20160905.1315Citation: Hu Y G, Zhao C, Liu P F, Asante E A, Li P P. Sprinkler irrigation system for tea frost protection and the application effect. Int J Agric & Biol Eng, 2016; 9(5): 17－23.